2021
DOI: 10.1016/j.jacep.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Hospital Cardiac Arrest Response and Outcomes During the COVID-19 Pandemic

Abstract: Objectives To evaluate the potential impact of the COVID-19 pandemic on out-of-hospital cardiac arrest (OHCA) response and outcomes in two US communities with relatively low infection rates. Background Studies in areas with high COVID-19 infection rates indicate that the pandemic has had direct and indirect effects on community response to OHCA and negative impacts on survival. Data from areas with lower infection rates are lacking. Methods I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
5
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 16 publications
4
82
5
10
Order By: Relevance
“…Similar patterns of increased OHCA incidence during COVID-19 have been reported from the USA, Paris, and Lombardia. 5 , 6 , 7 , 8 , 9 Taken together with the observation that a quarter of our OHCA patients either had, or were clinically suspected to have, COVID-19 our findings strongly support a link between COVID-19 and the occurrence of OHCA. Whether such a link is the direct result of the pathophysiology of the disease, or more widely related to indirect factors, such as a reluctance to access medical assistance for conditions pre-empting cardiac arrest, changes to healthcare provision and infrastructure, or even the societal restrictions that accompanied the pandemic, remains to be ascertained.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Similar patterns of increased OHCA incidence during COVID-19 have been reported from the USA, Paris, and Lombardia. 5 , 6 , 7 , 8 , 9 Taken together with the observation that a quarter of our OHCA patients either had, or were clinically suspected to have, COVID-19 our findings strongly support a link between COVID-19 and the occurrence of OHCA. Whether such a link is the direct result of the pathophysiology of the disease, or more widely related to indirect factors, such as a reluctance to access medical assistance for conditions pre-empting cardiac arrest, changes to healthcare provision and infrastructure, or even the societal restrictions that accompanied the pandemic, remains to be ascertained.…”
Section: Discussionsupporting
confidence: 81%
“…While the current literature provides a mixed picture regarding resuscitation rates and ROSC, five of the six studies published to date that have measured survival to hospital discharge, have reported decreases during COVID-19. 6 , 7 , 9 , 10 , 12…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the incidence out-of-hospital cardiac arrests has increased during the pandemic and cannot be entirely explained by COVID-19 ( 8 , 15 ). Recent evidence indicate that delays in emergency medical service response times and a reduction in bystander cardiopulmonary resuscitation rates have likely contributed to reduced survival after cardiac arrest ( 16 ). In contrast, we observed no increase in deaths caused by other cardiovascular conditions, such as heart failure, possibly because they often do not require emergent hospitalization for potentially life-saving treatment.…”
Section: Discussionmentioning
confidence: 99%